Epidemiological, clinical, and laboratory characteristics of 581 human brucellosis cases in Xinjiang, China - Luo, Bin; Wang, Qian; Yang, Shuting; Song, Xue; Li, Zhiwei (Frontiers in Microbiology, 2025)
BackgroundEpidemiological and clinical analyses of brucellosis are crucial for the development of surveillance and case management strategies.MethodsWe analyzed the epidemiological and clinical characteristics of 581 human brucellosis cases in Xinjiang. Demographic characteristics of patients with brucellosis and their clinical manifestations were collected and analyzed.ResultsAmong the 581 brucellosis patients, the men-to-women ratio was 2.8:1.0 (428:153); the age was (44.41 ± 16.25) years, ranging from 1 to 83 years, mainly concentrated in the 35–60 age group, accounting for 70.91% (412 cases); the ethnic distribution was mainly Uyghur, accounting for 50.60%; the occupational distribution was mainly farmers, accounting for 43.20%. A total of 186 patients had a clear history of contact with cattle and sheep breeding. Clinical staging was mainly chronic stage patients, accounting for 55.24% (321 cases), and there were 48 cases with complications, mainly pain and fatigue, accounting for 8.26%. The most common laboratory examination characteristics were increased erythrocyte sedimentation rate and increased C-reactive protein level, accounting for 29.09% and 23.06%, respectively, and the blood culture detection rate was low (4.48 %).ConclusionPatients with brucellosis in the Xinjiang Uyghur Autonomous Region predominantly comprised middle-aged and young men primarily involved in farming. The principal clinical symptoms include pain and fever; however, the positivity rate of Brucella cultures in these patients is low. To minimize the risk of missed diagnoses or misdiagnoses, it is recommended to integrate epidemiological history, clinical manifestations, and laboratory examination results into the diagnostic process to facilitate earlier detection and treatment.